(3GdCMcGe GdbGfhfjI ddYbhO GdEdcJQhfjI (B: s (3OQGSI ebGQfI (B/ s - (3UahGf MeRI EHQGgje YjSi GdghGQjs; (3SejMI eUWai GdbdjhHjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3JJfGhd gPg GdQSGdI GdCMcGe GdJj bQQJgG GdbhGfjf GdebGQfI Ydi GdeSJhjjf(B: (3GdOhdj(B: (3h GdhWfj; dJfXje GdYbhO GdEdcJQhfjI(B: (3ceG CfgG GYJeOJ CjVG aj JMOjO gPg GdCMcGe Ydi GdShGHb GdbVGFjI GdJj JYO HOhQgG ecedI ddfhGbU GdJj JdMb HGdfUhU GdJTQjYjI(B. (3h aj EWGQ ehVhY GdHMK befG HOQGSI eGgjI YbhO GdJLGQI GdEdcJQhfjI(B: (3h HjGf NUGFUgG(B: (3h WQb EHQGegG(B: (3h ChLg GdGJaGb HjfgG ef MjK GfYbGO GdYbO h UMJg eY GdbhGYO GdYGeI GdeYehd HgG h eOi MGLJgG Edi JfXje bGfhfj NGU HgG(B: (3ceG JfGhdJ GdQSGdI eOi edGFeI GdCMcGe GdNGUI HEKHGJ GdYbO GdEdcJQhfi ajeG jJYdb HGdeMQQGJ GdEdcJQhfjI h GdJhbjY GdEdcJQhfi aj Xd bGfhf GdJhbjY GdEdcJQhfi GdeUQj h GdbhGfjf GdebGQfIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2012s
(3HHdjhLQGajG(B: (3UaMGJ (B446-478s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdJLGQI GdEdcJQhfjIs; (3GdOaY GdEdcJQhfis; (3GdYbhO GdEdcJQhfjIs; (3GdJYGbO YHQ GdGfJQfJs; (3GdeMQQ GdGdcJQhfis; (3MeGjI GdeSJgdcs; (3JShjI efGRYGJ GdYbhO GdGdcJQhfjIs; (3gjFGJ GdJMcje GdGdcJQhfis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs